2009
DOI: 10.1073/pnas.0900284106
|View full text |Cite
|
Sign up to set email alerts
|

Translocation experiments with butterflies reveal limits to enhancement of poleward populations under climate change

Abstract: There is a pressing need to predict how species will change their geographic ranges under climate change. Projections typically assume that temperature is a primary fitness determinant and that populations near the poleward (and upward) range boundary are preadapted to warming. Thus, poleward, peripheral populations will increase with warming, and these increases facilitate poleward range expansions. We tested the assumption that poleward, peripheral populations are enhanced by warming using 2 butterflies (Ery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
148
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(158 citation statements)
references
References 51 publications
2
148
3
1
Order By: Relevance
“…Alternatively, it may be the case that the structure and dynamics of more temperate ant communities are not limited exclusively by temperature. Several studies now exist in which northern populations of insects do not experience changes in population sizes with warming (e.g., Adler et al 2007, Pelini et al 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, it may be the case that the structure and dynamics of more temperate ant communities are not limited exclusively by temperature. Several studies now exist in which northern populations of insects do not experience changes in population sizes with warming (e.g., Adler et al 2007, Pelini et al 2009). …”
Section: Discussionmentioning
confidence: 99%
“…Local adaptation to historical climates, and corresponding maladaptation to new climates, also may be more pronounced at high latitudes (Pelini et al 2009). Although individual organisms at low latitudes may be more sensitive to climatic change than those at high latitudes, ecological communities at low latitudes could be more resilient to environmental change because they are generally more diverse (Wittebolle et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In-depth breeding experiments are required, conducted under different microclimate conditions using individuals from the same clutch and these clutches have to be representative of different latitudes. In fact, it has been demonstrated that different populations respond differently to climate changes (Pelini et al 2012): they can be adapted to historically different conditions (Gilman et al 2006, Pelini et al 2009, Angert et al 2011 and have different abilities to cope with local environmental changes (Magnani 2009). However, as L. cervus has a long larval stage (3-6 years) which can vary significantly across its distribution (Harvey et al 2011), this makes these breeding experiments difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Predicting biological responses to climate change is critical (Arau´jo et al 2005), but a number of researchers have begun to emphasize the potential unpredictability of species' responses to climate change (e.g., Hill et al 2002, McGeoch et al 2006, Pelini et al 2009, Doak and Morris 2010. If species-specific traits covary with their responses to climate change, such traits can be used to predict community change (Diamond et al 2011, Angert et al 2011.…”
Section: Introductionmentioning
confidence: 99%